Uganda - Agriculture Public Expenditure Review - World Bank (World Bank, 2012)
This Agriculture Public Expenditure Review (AgPER) comprehensively reviews public expenditures on agriculture in Uganda and analyzes their efficiency and effectiveness. Its genesis lies in Agriculture Sector Working Group (A-SWG) discussions, especially during the budget process, which raised concerns about the seemingly low budget allocations to the sector and the failure to align limited resources with recognized priorities in the sector. To address these concerns, the A-SWG resolved to undertake this AgPER. Aside from providing a better understanding of the nature and composition of agricultural pubic expenditures in Uganda, the review will specifically analyze their efficiency and effectiveness with a view to identifying the types of expenditures that will promote pro-poor growth. The report is structured as follows. Section two analyzes trends in nominal and real sector budgets. It highlights the current and projected importance of agricultural sector expenditure in the national budget and gross domestic product (GDP). An analysis of agricultural price distortions indicates the extent to which the sector benefits from supportive policies. Section three describes budget planning and implementation at the national and local level and presents policy recommendations to improve those processes. Section four focuses on the technical efficiency of public spending. By tracking resource flows and analyzing the unit costs of goods and service delivery. Section four sheds light on whether public resources are used efficiently and which actions could improve efficiency. The concluding section summarizes the major findings and policy recommendations.